Penerapan Model Pembelajaran Project Based Learning pada Outdoor Study Materi Seni Lukis sebagai Upaya Meningkatkan Hasil Belajar Siswa Kelas XII IPA 1 SMA Pertiwi 1 Padang - Saputri, Delia; Sandra, Yofita (AHKAM, 2025)
This type of research is classroom action research (PTK). The subjects of this research were students of class. This research is motivated by the problem of student learning outcomes. This research was carried out in two cycles, with two meetings in each cycle. Data collection in this research used teacher observation sheets, student observation sheets and evaluation sheets of student learning outcomes (tests and projects). This research aims to improve student learning outcomes in learning painting using the project based learning model in outdoor study at SMA Pertiwi 1 Padang. The results obtained in this research show that the Project based learning model in outdoor study can improve learning outcomes in fine arts subjects, especially painting material for class Completion in the pre-cycle was very low with a percentage of 30.6%, increasing in cycle I with a percentage of 72.2% of students completing and increasing in cycle II to 94.4%. Thus, it can be concluded that by applying the Project based learning model in outdoor study, it can improve learning outcomes for class XII IPA 1 on painting art material.